Velocity-free fault tolerant control allocation for flexible spacecraft with redundant thrusters - Hu, Qinglei (2013)
This paper proposes a novel velocity-free nonlinear proportional-integral (PI) control allocation scheme for fault tolerant attitude control of flexible spacecraft under thruster redundancy. More specifically, the nonlinear PI controller for attitude stabilization without using body angular velocity measurements is firstly designed as virtual control of a control allocator to produce the three axis moments, and can guarantee uniform ultimately boundedness of the closed-loop system in the presence of external disturbances and possible stuck faults. The associated stability proof is constructive and accomplished by the development of a passivity filter formulations together with the choice of a Lyapunov function containing cross/mixed terms involving the various states. Then, a robust least squares based control allocation is employed to deal with the problem of distributing the three axis moments over the available thrusters under redundancy, in which the focus of this control allocation is to find the optimal control vector of actuator by minimizing the worst-case residual, under the condition of thruster faults and control constraints like saturation.